2022
DOI: 10.3390/ani12233361
|View full text |Cite
|
Sign up to set email alerts
|

Performance, Egg Quality, and Yolk Antioxidant Capacity of the Laying Quail in Response to Dietary Choline Levels

Abstract: The current study determined the ideal dose of choline in the diet of laying quails based on egg development, egg quality, and antioxidant capacity. A total of 120 female quails (244.7 ± 10.38 g) were randomly assigned to 6 experimental groups with 5 replicates of 4 quails each. In the 10-week trial, treatment diets were formed by adding 6 choline chloride−60% concentrations providing 1500 (control), 2000, 2500, 3000, 3500, and 4000 mg/kg of choline. The feed intake of quails was quadratically affected (p <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 32 publications
0
10
1
Order By: Relevance
“…These findings are consistent with the results reported by Park and Ryu (2011) and Sadegheymojarad et al (2018) for betaine addition. However, these results disagreed with previous authors who suggested that the administration of choline ( Moghadam et al, 2021 ; Olgun et al, 2022 ) or betaine ( Ratriyanto et al, 2017 ; Rasul et al, 2019 ) has positive effects on performance and egg production. Many reasons could justify the disagreement between the different studies.…”
Section: Discussioncontrasting
confidence: 98%
See 4 more Smart Citations
“…These findings are consistent with the results reported by Park and Ryu (2011) and Sadegheymojarad et al (2018) for betaine addition. However, these results disagreed with previous authors who suggested that the administration of choline ( Moghadam et al, 2021 ; Olgun et al, 2022 ) or betaine ( Ratriyanto et al, 2017 ; Rasul et al, 2019 ) has positive effects on performance and egg production. Many reasons could justify the disagreement between the different studies.…”
Section: Discussioncontrasting
confidence: 98%
“…The nutritional requirements of animals have been modified due to changes and advances in dietary components and genetics. This situation leads to evaluating the requirements of certain ingredients and additives used in the diet ( Murawska et al, 2018 ; Olgun et al, 2022 ). In addition, some production tendencies (such as organic production) restrict the use of synthetic additives, being necessary to develop alternative feeding strategies ( Demattê Filho et al, 2015 ; Burley et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations